The Restoration of the Function of the Thumb using Sequential Arthroplasty of the Trapeziometacarpal and Metacarpophalangeal Joints - V. M. Prokhorenko; T. I. Aleksandrov; E. N. Simonova (Acta Biomedica Scientifica, 2020)
Background. The opposition function of the thumb is extremely important and is provided mainly due to the biomechanical features of the trapeziometacarpal and metacarpophalangeal joints. Surgical treatment of complex deformities of these joints is often described in isolated studies, and there are practically no descriptions of the results of their combined treatment. The authors of the article did not find a single report on total arthroplasty of the adjacent joints of the thumb.Aim of the study. To analyze the clinical observation of two patients in the early period after performing sequential non-simultaneous total arthroplasty of the trapeziometacarpal and metacarpophalangeal joints of the thumb using ceramic endoprostheses. Both endoprostheses were presented in pairs with two unconnected components, installed using the press-fit method. When the head and cup interact, there are no shear forces in them that impede multiaxial movements.Materials and methods. The study included two patients: a 67-year-old man and a 77-year-old woman. Patients had stage 3 osteoarthritis of the trapeziometacarpal and metacarpophalangeal joints of the thumb and underwent staged surgical treatment (about 2–3 years between the stages). In 1 month and 1 year after the treatment we assessed the results using clinical and instrumental research methods.Conclusion. No complications were observed during the follow-up. There were no indications for revision surgery. The design features of ceramic endoprostheses, due to their short stems, make it possible to combine components in the adjacent joints of the thumb. In our opinion, joint arthroplasty is an effective and promising method of functional restoration. It remains the patient’s last hope for maintaining painless, stable mobility of the thumb.